On Action Algebras - Kozen, Dexter (DAIMI Report Series, 1992)
Action algebras have been proposed by Pratt as an alternative to Kleene algebras. Their chief advantage over Kleene algebras is that they form a finitely-based equational variety, so the essential properties of *(iteration) are captured purely equationally. However, unlike Kleene algebras, they are not closed under the formation of matrices, which renders them inapplicable in certain constructions in automata theory and the design and analysis of algorithms. In this paper we consider a class of action algebras called action lattices. An action lattice is simply an action algebra that forms a lattice under its natural order. Action lattices combine the best features of Kleene algebras and action algebras: like action algebras, they form a finitely-based equational variety; like Kleene algebras, they are closed under the formation of matrices. Moreover, they form the largest subvariety of action algebras for which this is true. All common examples of Kleene algebras appearing in automata theory, logics of programs, relational algebra, and the design and analysis of algorithms are action lattices.